Maritime Fiction - Peck, J. author. aut Link
IX, 214 p.
Keywords: In this important new study, John Peck examines the cultural significance of maritime novels from Defoe through to Conrad. Focusing in particular on the image of the body, he illustrates how these works are built around the disparity between the masculine and often brutal regime of the ship and the civilised values of those who remain on the shore. The first comprehensive discussion of its subject, Maritime Fiction is an original exploration of the relationship between national identity, fiction and the sea.